Analisis Ergonomika Pengoperasian Bagian Pencacah pada Mesin Pencacah Pakan Ternak Multiguna - Ayu Anggiana; Siti Suharyatun; Febryan Kusuma Wisnu; Warji Warji (abe.fp.unila.ac.id, 2023)
The multi-purpose animal feed chopping machine is one of the feed chopping tools that many farmers use to help speed up the chopping of raw materials that will be used as animal feed. The chopping machine can be operated optimally if the machine is ergonomic so that it is safe and comfortable to operate. This study aims to analyze the ergonomics of a multi-purpose animal feed chopper in terms of anthropometry, operating workload and the level of work fatigue specifically for the chopper. This research uses quantitative methods which are supported by literature studies regarding the design of creating machine dimensions. The parameters in this study are: (1) anthropometric data consisting of Standing Finger Tip Height (TJUB), Standing Vertical Reach (JVB), and Standing Horizontal Reach (JHB); (2) the recommended weight limit that can be lifted by the operator (RWL), and (3) cardiovascular load (CVL). The research results stated that the height of the chopper hopper (100 cm) was classified as ergonomic because it was still between TJUB (66.10 cm) and JVB (183.95 cm). The operator's position from the hopper should not exceed JHB (66.00 cm). The recommended load limit (RWL) is 5.38 kg. Operation of the machine chopper section does not cause work fatigue with an average CVL of 10.71% (≤ 30%). Keywords: Anthropometry, CVL, Pulse Rate, RWL, Work Fatigue.